Redescription of Gymnorhynchus isuri (Cestoda: Trypanorhyncha) from Isurus oxyrinchus (Elasmobranchii: Lamnidae) - Knoff, Marcelo; Clemente, Sérgio Carmona de São; Pinto, Roberto Magalhães; Lanfredi, Reinalda Mariza; Gomes, Delir Corrêa (Folia parasitologica, 2007)
Specimens of the elasmobranch, Isurus oxyrinchus Rafinesque, captured in 1999 in the state of Santa Catarina, Brazil, were parasitized with the poecilacanthoid trypanorhynch cestode Gymnorhynchus isuri Robinson, 1959, that is redescribed here. New details of scolex and proglottid morphology are given. These details are mainly related to tentacle armature, terminal genitalia and observations of external morphology of proglottids.
Keywords: nemoci ryb; Animals; Fish Diseases; Cestode Infections; Elasmobranchii; zvířata; cestodózy; Cestoda